Complexing‐Coprecipitation Method to Synthesize Catalysts of Cobalt, Nitrogen‐Doped Carbon, and CeO2 Nanosheets for Highly Efficient Oxygen Reduction. Issue 6 (29th April 2019) - Wang, Xiaoqing; Xu, Jijian; Wu, Zongxiao; Zhi, Mingjia; Hong, Zhanglian; Huang, Fuqiang
Abstract: The oxygen reduction reaction (ORR) is the key cathode reaction in renewable‐energy technologies. Developing highly efficient, low‐cost, methanol‐tolerant and durable ORR catalysts is highly needed. In this research, we reported a simple complexing‐coprecipitation method to synthesize CeO2 nanosheets encapsulated by a nitrogen‐doped carbon (NC) layer with uniformly dispersed Co nanoparticles catalysts on the surface. In particular, the 0.5Co‐NC‐CeO2 sample exhibits high ORR catalytic activity with an onset potential of 875 mV (vs. RHE), a diffusion‐limited current density of 4.72 mA/cm 2 and a positive half‐wave potential of 817 mV (vs RHE), while 20% Pt/C presents an onset potential of 934 mV (vs. RHE), a diffusion limited current density of 5.8 mA/cm 2 and half‐wave potential of 850 mV (vs. RHE). In addition, the catalyst 0.5Co‐NC‐CeO2 also possesses a robust durability, that is the half‐wave potential exhibits a negative shift of only 17 mV after 1000 cycles. The enhanced ORR performance can be attributed to the synergistic effect among Co, the nitrogen‐doped carbon layer and CeO2 . The results demonstrated here have implications in designing non‐Pt ORR catalysts. Abstract : Triple threat : The ternary catalyst Co‐NC‐CeO2 was synthesized via a simple 'one‐pot' and 'one‐step' method. This catalyst exhibited excellent ORR performance, with a half‐wave potential of 817 mV (vs. RHE), a diffusion limited current density of 4.72 mA cm −2, and a good durability (half‐wave potential exhibiting a negative shift of only 17 mV after 1000 cycles), due to the synergistic effects between Co nanoparticles, the nitrogen‐doped carbon (NC) layer and CeO2 nanosheets.